Assessing training needs in infectious disease management at major ports, airports and ground-crossings in Europe - Doret de Rooij; Evelien Belfroid; Christos Hadjichristodoulou; Varvara A. Mouchtouri; Jörg Raab; Aura Timen; for the EU HEALTHY GATEWAYS Joint Action consortium (BMC, 2021)
Abstract Background The implementation of core capacities as stated in the International Health Regulations (IHR) is far from complete, and, as the COVID-19 pandemic shows, the spreading of infectious diseases through points of entry (POEs) is a serious problem. To guide training and exercises, we performed a training needs assessment on infectious disease management among professionals at European POE. Methods We disseminated a digital questionnaire to representatives of designated airports, ports, and ground-crossings in Europe. Topics were derived from the IHR core capacities for POEs. Based on the importance (4-point Likert scale) and training needs (4-point Likert scale), we identified the topics with the highest priority for training. These results were put in further perspective using prior experience (training < 3 year, exercise < 5 years, events < 5 years). Also, preferences for training methodologies were assessed. Results Fifty questionnaires were included in the analyses, representing 50 POEs from 19 European countries. Importance is high for 26/30 topics, although scores widely vary among respondents. Topics with a high training need (16/30) are amongst others the handling of ill travelers; using and composing the public health emergency contingency plan, and public health measures. Respondents from ports and airports attribute equal importance to most topics, but respondents from ports showed higher training needs on 75% of the topics. POEs are unevenly and generally little experienced. The most preferred training methods were presentations. Simulation is the preferred methodology for training the handling of ill or exposed travelers. Conclusions The European workforce at designated ports, airports and ground-crossings has a different level of experience and perceives varying importance of the topics assessed in our study. We identified the topics on which training is required. We call for European collaboration between POEs to agree upon the importance of infectious disease management, and to jointly build a trained and prepared workforce that is ready to face the next crisis.